Stress and Turnover in the Ed-tech Industry - Raj, Piyush (Ushus Journal of Business Management, 2024)
This research aims to explore the relationship between job stress and intention to leave in the Educational Technology (EdTech) industry, with a specific focus on how job commitment mediates this relationship. The study involved conducting surveys among EdTech employees to gather quantitative data. The results show a significant positive correlation between stress and intention to quit, as well as a negative correlation between job stress and job commitment. Additionally, it was found that commitment partially mediated the impact of stress on intention to quit. The findings highlight the importance of promoting job commitment to reduce turnover intentions resulting from job stress in the EdTech industry.